2020
DOI: 10.3390/s20061632
|View full text |Cite
|
Sign up to set email alerts
|

Secrecy Performance Analysis of Wireless Powered Sensor Networks Under Saturation Nonlinear Energy Harvesting and Activation Threshold

Abstract: In this paper, we investigate the impact of saturation nonlinear energy harvesting (EH) and activation threshold on the multiuser wireless powered sensor networks (WPSNs) from the physical layer security (PLS) perspective. In particular, for improving the secrecy performance, the generalized multiuser scheduling (GMS) scheme is exploited, in which the Kth strongest sensor is chosen based on the legitimate link. For evaluating the impact of various key parameters on the security of system, we obtain the exact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The following section illustrates the comparative analysis of the proposed model with other existing models. This graph compares the proposed method to other prevailing approaches such as random user scheduling (RUS) scheme and best user scheduling (BUS) scheme [37]. It is observed that the proposed proportional max-min fairness (PMMF) method has obtained netter secrecy performance when compared to BUS and RUS schemes.…”
Section: Resultsmentioning
confidence: 96%
“…The following section illustrates the comparative analysis of the proposed model with other existing models. This graph compares the proposed method to other prevailing approaches such as random user scheduling (RUS) scheme and best user scheduling (BUS) scheme [37]. It is observed that the proposed proportional max-min fairness (PMMF) method has obtained netter secrecy performance when compared to BUS and RUS schemes.…”
Section: Resultsmentioning
confidence: 96%
“…Another tiny wireless sensor network operating system is developed by the us at the University of Colorado MANTIS OS, It supports fast and flexible architecture of wireless sensor network (WSN). The operating system how to automatic configuration, adaptive to support the needs of the wireless sensor network, it is still an open research problem [6].…”
Section: Operating Systemmentioning
confidence: 99%
“…To achieve this optimization, T x and R x cannot utilize the swift CSI at Eve, so as earlier mentioned, P R is inappropriate for this optimization. From some previous research [6,13,18], it is observed that Eve's symptotic rate is a decent approximation to the tangible rate; thus, we adopted this fact in order to achieve optimization. Suppose that the we make no assumption on the realizable random parameter (r) and assuming that z r is a vector encompassing the transverse elements of Z r , and (A E ) is discreetly huge.…”
Section: Optimization Of Swift Privacy Rate In a Mimomementioning
confidence: 99%
“…That being said, a lot of attention has been drawn towards the security of the physical (PHY) layer lately. From a PHY security perspective, the authors of [6] investigated the impact of saturation nonlinear energy harvesting (EH) and activation threshold on the multiuser wireless powered sensor networks (WPSNs) from the physical layer security (PLS) perspective, and with respect to the generalized multiuser scheduling (GMS), they examined the improvement in the secrecy performance in WPNs. Their work explored and presented an exact closed-form expressions for secrecy outage probability (SOP) under linear EH (LEH), saturation nonlinear EH (SNEH), and saturation nonlinear EH with activation threshold (SNAT), respectively, through finding a solution for the maximization problem of secure energy efficiency (SEE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation